Underground Ventilation : PROCEEDINGS OF THE 19TH NORTH AMERICAN MINE VENTILATION SYMPOSIUM (NAMVS 2023), 17-22 JUNE 2023, RAPID CITY, SOUTH DAKOTA, USA - Tukkaraja, Purushotham (CRC Press/Balkema, 2023)
Underground Ventilation contains the proceedings of the 19th North American Mine Ventilation Symposium held at the South Dakota School of Mines & Technology (South Dakota Mines) in Rapid City, South Dakota, June 17-22, 2023. South Dakota Mines organized this symposium in collaboration with the Underground Ventilation Committee (UVC) of the Society for Mining, Metallurgy & Exploration (SME). The Mine Ventilation Symposium series has always been a premier forum for ventilation experts, practitioners, educators, students, regulators, and suppliers from around the world to exchange knowledge, ideas, and opinions. Underground Ventilation features sixty-seven selected technical papers in a wide range of ventilation topics including: auxiliary and primary systems, mine fans, case studies, computational fluid dynamics applications, diesel particulate control, electric machinery, mine cooling and refrigeration, mine dust monitoring and control, mine fires and explosion prevention, mine gases, mine heat, mine ventilation and automation, occupational health and safety, renewable/alternative energy, monitoring and measurement, network analysis and optimization, and planning and design